Crystal structures and biological activity of 1,1,4-triphenyl-substituted 1,3-enyne compounds - Pineda Cedeño, Leslie William (2019)
1,3-Enyne structural motifs are versatile building blocks in organic synthesis and occur widely in various natural products with many of them being highly active as cytotoxic macrolides and antitumour antibiotics. This article presents the crystal structure of three 1,1,4-triphenyl-substituted 1,3-enynes, viz. 4-(2- methylphenyl)-1,1-diphenylbut-1-en-3-yne, C23H18 (1), 4-(2-methoxyphenyl)-1,1- diphenylbut-1-en-3-yne, C23H18O (2), and 4-(4-nitrophenyl)-1,1-diphenylbut-1- en-3-yne, C22H15NO2 (3). The benzene ring at position 4 of the but-1-en-3-yne group bears a weakly activating methyl group in compound 1, a moderately activating methoxy group in 2 and a strongly deactivating nitro group in 3. The crystal structures of 1 and 3 both have monoclinic symmetry, while that of 2 is orthorhombic, and all of them have one molecule in the asymmetric unit. All three compounds were investigated for their antibacterial and antifungal activities. Interestingly, enyne 2 is the only compound tested that inhibited the growth of Aspergillus niger.